2010
DOI: 10.1159/000322211
|View full text |Cite
|
Sign up to set email alerts
|

Macroorchidism and Panhypopituitarism: Two Different Forms of Presentation of FSH-Secreting Pituitary Adenomas in Adolescence

Abstract: Background: FSH-secreting pituitary adenomas are extremely rare in children and are seldom associated with clinical manifestations of high serum gonadotrophin levels. Thus, most patients have a late presentation, usually as macroadenomas. Case Reports: Two different clinical forms of presentation of FSH-secreting pituitary adenomas are reported: one in a 12-year-old boy with macroorchidism due to a pituitary microadenoma, probably FSH-secreting, and the other in a 15-year-old boy with panhypopituitarism due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
1
13
0
2
Order By: Relevance
“…Both processes involve TSH beta ( TSHB ) gene expression and TSH glycosylation respectively, and both are known to be dependent on TRHR activation2021. On the other hand, the patient presented with excessive FSH secretion as a neonate which, interestingly, resulted in macroorchidism, as happens in FSH-secreting pituitary adenomas252627. FSH secretion is critically regulated by testicular inhibin B through inhibition of the stimulatory activin-Smad signaling pathway, and IGSF1 was proposed as a putative inhibin B receptor7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both processes involve TSH beta ( TSHB ) gene expression and TSH glycosylation respectively, and both are known to be dependent on TRHR activation2021. On the other hand, the patient presented with excessive FSH secretion as a neonate which, interestingly, resulted in macroorchidism, as happens in FSH-secreting pituitary adenomas252627. FSH secretion is critically regulated by testicular inhibin B through inhibition of the stimulatory activin-Smad signaling pathway, and IGSF1 was proposed as a putative inhibin B receptor7.…”
Section: Resultsmentioning
confidence: 99%
“…5B) based on the pituitary de-repression of FSHB transcription at pituitary gonadotropes and the postnatal over-secretion of FSH at mini-puberty, which may lead to premature proliferation of testicular Sertoli cells49, a known cause for macroorchidism in children and adults with FSH-secreting pituitary adenomas252627. These findings are relevant since all IGSF1-deficient patients so far identified with macroorchidism were adolescents and adults4, which has prevented the elucidation of the precise chronology for testicular growth in this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Most are FSH-secreting adenomas [2,57]. The diagnosis is typically delayed until the appearance of symptoms related to tumour mass or pituitary hormone deficiency.…”
Section: Individual Adenomasmentioning
confidence: 99%
“…The diagnosis is typically delayed until the appearance of symptoms related to tumour mass or pituitary hormone deficiency. Patients may present with macro-orchidism, ovarian cysts or precocious puberty due to FSH hyperstimulation [2,57]. Diagnosis is based on increased levels of FSH and inhibin B, with normal or low luteinising hormone and testosterone, an increased FSH response to gonadotropin-releasing hormone stimulation, detection of a pituitary mass on MRI, and immunohistochemical confirmation of the surgical specimen [57].…”
Section: Individual Adenomasmentioning
confidence: 99%
“…Surgical removal of the adenoma remains the optimal approach, and when successful, it leads to restoration of normal gonadotropin secretion. Treatment with dopamine agonists, long-acting somatostatin analogues, and GnRH agonists and antagonists has been used with inconsistent results and is thus not recommended as a primary therapeutic approach (13). Occasional case reports have shown that dopamine agonists may reduce autonomous FSH secretion and help complete a pregnancy or improve ovarian hyperstimulation syndrome (14,15).…”
mentioning
confidence: 99%